Pemenuhan Nafkah Istri Yang Ditinggal Suami Untuk Menjadi TKI - Syahputra Sitorus, Ria Ganda; Abd. Mukhsin (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Marriage is about mutually obtaining rights and obligations and aims to establish a social relationship based on mutual help because marriage includes the implementation of religion, so it contains this. The goal/intent is to hope for the pleasure of Allah SWT, but sometimes in the household the economic situation becomes an obstacle in itself so that the husband decides to go as a migrant worker and leave his wife. The aim of this research is to find out what the law is regarding fulfilling the livelihood of a wife whose husband left her to become a migrant worker in the sense of fulfilling non-material (mental) livelihood which cannot be distributed. This research method uses a qualitative research method with a descriptive approach. The results in this study show that a TKI who leaving his wife with the obligation to provide non-material support. This can be circumvented by TKI who work abroad by taking leave rights in accordance with article 73 paragraph (1) of Law no. 39 of 2004 concerning Placement and Protection of Indonesian Workers Abroad. In addition, from the results of the interview as a whole, it can be concluded that they have worked as husband and wife to meet their inner needs, namely by being open to each other about the needs of intimate relationships, as well as understanding and accepting each other the situations that occur as part of the journey of life through intense communication, either through telephone, video call, or text